The Moral Mystic - Horne, James R. (Book collections on Project MUSE., 2006)
Mysticism is condemned as often as it is praised. Much of the condemnation comes from mysticism's apparent disregard of morality and ethics. For mystics, the experience of ""union"" transcends all moral concern. In this careful examination of the works of such practitioners or examiners of mysticism as Paul Tillich, Thomas Merton, Evelyn Underhill, and Martin Buber, the author posits a spectrum of uneasy relationships between mysticism and morality. Horne explores the polarities of apophatic (imageless) and imaginative mysticism, the contemplative and the active life, and morality and amoral.